Cutoff values for strength asymmetry classification on soccer players - Araújo, S. R. S.; Abreu, E. A. C.; Menzel, H. K.; Medeiros, F. B. (Revista Brasileira de Medicina do Esporte, 2024)
Introduction: Strength asymmetry in soccer players may arise from unilateral demands along years of training and may be related to higher injury risk and performance impairment. However, cut-off values used to classify asymmetry can be different among tests or outcomes. Objective: The aim was to compare the distribution of soccer players classified as symmetric or asymmetric based on the arbitrary cut-off value of 15% and the Upper Limit Value method for impulse and peak force. Methods: 184 professional Brazilian soccer players did the countermovement jump test on two force plates. The symmetry index was used to quantify the asymmetry of peak force and impulse. Then, cut-off value of 15% was compared with the cut-off value estimated from the Upper Limit Value. McNemar Chi² test was used to verify the concordance of diagnostic. Results: Upper Limit Value for peak force and impulse asymmetries were 10.86% and 25.31%, respectively. McNemar Chi² test confirmed the hypothesis, that the classification of athletes would be statistically different between cut-off values. Conclusions: We concluded that cut-off values based on Upper Limit Value for impulse and peak force were different from the 15% cut-off values. Coaches should be aware of this different classification choosing the cut-off value that best fits their team. Level of Evidence II; Diagnostic Studies-Investigation of a Diagnostic Test.